Peran Guru dalam Meningkatkan Kedisiplinan Peserta Didik di Kelas VI SDN Kebon Jeruk 11 Pagi: Penelitian - Manjakani, Anggun; Mujazi, Mujazi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is motivated by the issue of discipline in schools, which is an important part of character education to shape a superior generation of Indonesia. Discipline reflects the process of individual character formation related to values, attitudes, and behaviors that have a positive impact on oneself, the environment, and society. This study aims to determine the role of teachers in improving the discipline of sixth-grade students at SDN Kebon Jeruk 11 Pagi. The method used is qualitative with observation, interviews, and documentation techniques. Data analysis was conducted descriptively according to the conditions found without generalization. The results of the study indicate that character education is very important and needs to involve schools and parents, for example through recording discipline discussed in parent forums. Teachers also need to instill discipline through a good teaching style and attitude, and help students recognize themselves.